2003
DOI: 10.1148/radiol.2271020198
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Motion Depicted at Cine MR Imaging Performed during Sleep: Comparison between Young Patients with and Those without Obstructive Sleep Apnea

Abstract: There are significant differences in the patterns of dynamic airway motion between young patients with and those without OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 31 publications
1
59
0
6
Order By: Relevance
“…The limitations of fluoroscopy are both radiation exposure and that one obtains only a plane lateral image. More recently, Donnelly and coworkers (24,25) applied ungated cine MRI to children with OSAS with complex medical conditions. They demonstrated significant fluctuations in airway size during respiration in subjects with OSAS along the entire upper airway compared with control subjects, a finding that is compatible with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of fluoroscopy are both radiation exposure and that one obtains only a plane lateral image. More recently, Donnelly and coworkers (24,25) applied ungated cine MRI to children with OSAS with complex medical conditions. They demonstrated significant fluctuations in airway size during respiration in subjects with OSAS along the entire upper airway compared with control subjects, a finding that is compatible with our results.…”
Section: Discussionmentioning
confidence: 99%
“…28 Donnelly et al reported significant differences in the patterns of airway dynamic motion when they compared young OSA patients with subjects without OSA using 3-D imaging. 29 CBCT are now being routinely taken from a cohort of patients receiving orthodontic treatments, TMJ surgeries and dental implant evaluations. Even though CBCT does not have the highest resolution compared to traditional CT scans, its low radiation exposure allows utilization on a variety of clinical patients to collect data for more longitudinal studies.…”
Section: -D Evaluationmentioning
confidence: 99%
“…Other limitations of CT and MRI include motion artifact due to tidal breathing or active airway obstruction, the need for sedation in infants and young children to prevent motion artifact, and cost. Dynamic respiration-gated techniques with CT and MRI have been recently introduced by several groups to study airway dynamics, and may provide functional data based on measures of collapsibility (62,63). The utility of such imaging techniques, along with computation models of upper airway fluid and tissue mechanics are beginning to provide better understanding of the complex anatomical and functional interactions leading to OSAS and other respiratory disorders in both children and adults.…”
Section: Evaluation Of the Upper Airway Using Imaging And Other Technmentioning
confidence: 99%